“It’s Something That We All Need to Know”: Australian Youth Perspectives of Mental Health Literacy and Action in Schools - Marinucci, Alexandra; Grové, Christine; Rozendorn, Goldie (Frontiers in Education, 2022)
Young people expressed concern about their mental health before COVID-19, and these concerns have escalated in response to the pandemic. A lack of knowledge, stigma and unfamiliarity with how to seek help contribute to low self-efficacy in mental health care. There is a need for school settings to include mental health education, or mental health literacy (MHL), to address youth mental health needs. Evaluation of school-based MHL programs often occur without the consultation of key stakeholders, such as young people. This study aimed to understand young people’s experience of mental health education in their school and their perspectives of how future mental health education can be tailored to suit their needs. Four online group discussions were conducted with 13 participants aged 11 to 18 years old. Eight main themes were generated from these discussions: (1) limited mental health education and understanding in school, (2) struggle to help seek, (3) negative mental health attitudes, (4) desired content about mental health education, (5) understanding of mental health, (6) school as a place for support, (7) suggestions for mental health education, and (8) ways for schools to be responsive to youth needs. All the young people in this study expressed concerns around the lack of mental health education in their schools and indicated that this must change for the wellbeing of all youth.